0219 Interplay of School Days and Free Days with Sleep Midpoint on the Association of Visceral Adiposity with Blood Pressure in Adolescents. (25th May 2022) - Morales-Ghinaglia, Natasha; Larsen, Michael; Calhoun, Susan; He, Fan; Liao, Jason; Vgontzas, Alexandros; Bixler, Edward; Liao, Duanping; Fernandez-Mendoza, Julio
Abstract: Introduction: The circadian timing of sleep, including its variability, has emerged as an important contributor to obesity and cardiovascular health, such as elevated blood pressure. Adolescence is a particularly vulnerable period for circadian misalignment, which may express differently if youth are in school or on free-days. We examined whether deviations in sleep midpoint increase the impact of visceral adiposity on elevated blood pressure in adolescents as a function of being entrained to school or not. Methods: We analyzed cross-sectional data from the Penn State Child Cohort follow-up study, a random population-based sample of 303 adolescents (16.2 ± 2.2 y; 47.5% female; 21.5% minority). Actigraphy-measured sleep midpoint was calculated as the midpoint (zeroed to midnight) of the sleep period for weekdays (5-nights) and weekends (2-nights). Actigraphy-measured sleep regularity was calculated as the intra-individual standard deviation of the 5-night weekdays sleep midpoint. Visceral adipose tissue (VAT) was measured via dual-energy X-ray absorptiometry scan. Systolic (SBP) and diastolic (DBP) blood pressure was measured three times in the seated position. Multivariable linear regression models were stratified by "in school" and "on break" to test sleep midpoint and sleep regularity as effect modifiers of VAT on SBP/DBP levels. Analyses were adjusted for sex, race/ethnicity, age, actigraphy-measured sleep duration and polysomnography-measured apnea/hypopnea index. Results: When participants were studied while "in school", significant interactions were found between VAT and weekdays sleep midpoint on SBP (p-interaction=0.027) and DBP (p-interaction=0.046), so that the later the sleep midpoint on school days, the greater the association of VAT with SBP/DBP. When participants were studied while "on break", a significant interaction was found between VAT and weekdays sleep regularity on SBP (p-interaction=0.039), so that the higher the sleep irregularity on weekdays, the greater the association of VAT with SBP. No other significant interactions were found. Conclusion: A delayed and an irregular sleep midpoint during school days and during breaks, respectively, best identified those adolescents with greater cardiovascular risk associated with visceral obesity. These data suggest that not only the circadian timing of sleep contributes to adverse cardiovascular outcomes but its distinct biomarkers require measurement under different entrainment conditions in adolescents. Support (If Any): National Institutes of Health (R01HL136587, UL1TR000127)